2005
DOI: 10.21861/hgg.2005.67.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Geography of Religion – Rediscovering a Subdiscipline

Abstract: Review Pregledni članakIn many parts of the world, the significance of religion has increased during the last years and decades. In the sociology of religion, the secularization thesis was the dominant framework for the interpretation of developments in the realm of religion for a long time. Meanwhile, other explanation patterns have become more prominent, such as the individualization thesis and economic theories. The so-called "spatial turn" does not seem to have reached sociology of religion yet. In history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 62 publications
0
12
0
7
Order By: Relevance
“…What is certainly necessary, however, is that the German society accepts the fact that meanwhile it has become an immigration society. In a recent survey on new developments in the geography of religions (Henkel 2005a), it was found that there is relatively little geographical literature on issues of state-religion relationship so far. The process of Europe growing together is a field where geographers and others familiar with and interested in the national religious structures and developments in the context of political and social trends can find a fruitful study topic in the future.…”
Section: Resultsmentioning
confidence: 99%
“…What is certainly necessary, however, is that the German society accepts the fact that meanwhile it has become an immigration society. In a recent survey on new developments in the geography of religions (Henkel 2005a), it was found that there is relatively little geographical literature on issues of state-religion relationship so far. The process of Europe growing together is a field where geographers and others familiar with and interested in the national religious structures and developments in the context of political and social trends can find a fruitful study topic in the future.…”
Section: Resultsmentioning
confidence: 99%
“…For one notable exception on the legal geography of religion in US and Canadian public schools, see Collins (2006Collins ( , 2007. On the geography of secularization, see Henkel (2005), Knippenberg (2005), and Knippenberg et al (2006). 5 I am inspired in part by Kenneth Foote's (1997) useful typology of sanctification, designation, rectification, and obliteration.…”
Section: Secular Iconoclasm 651mentioning
confidence: 99%
“…1 The transformation in the signi fi cance of religion in practice as well as in theory is by now a familiar thesis and may be illustrated by the following events we witnessed. Henkel 2005 ) . Each proposal was to recognise and selectively incorporate from around 100 items of immigration policy of interest to government.…”
Section: Introductionmentioning
confidence: 99%